2014
DOI: 10.2147/oajsm.s38599
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the regulation of pacing: current perspectives

Abstract: During prolonged dynamic and rhythmic exercise, muscular pain and discomfort arises as a result of an increased concentration of deleterious metabolites. Sensed by peripheral nociceptors and transmitted via afferent feedback to the brain, this provides important information regarding the physiological state of the muscle. These sensations ultimately contribute to what is termed “exercise-induced pain”. Despite being well recognized by athletes and coaches, and suggested to be integral to exercise performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 50 publications
3
56
0
1
Order By: Relevance
“…Because the tDCS intervention did not induce analgesia to exercise-induced pain, this lack of effect is to be expected. It has previously been suggested that exerciseinduced pain could moderate exercise intensity or pacing strategy, which may affect the final outcome of performance (Mauger 2013(Mauger , 2014Mauger et al 2010). Accordingly, by reducing perceived pain or increasing pain threshold, an athlete should be able to improve their performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the tDCS intervention did not induce analgesia to exercise-induced pain, this lack of effect is to be expected. It has previously been suggested that exerciseinduced pain could moderate exercise intensity or pacing strategy, which may affect the final outcome of performance (Mauger 2013(Mauger , 2014Mauger et al 2010). Accordingly, by reducing perceived pain or increasing pain threshold, an athlete should be able to improve their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with afferent feedback during intense exercise is the stimulation of muscle nociceptors and the subsequent perception of pain and discomfort. This exercise-induced pain has been suggested to play an important role in work rate selection and thus consequently affect endurance performance (Mauger et al 2010;Mauger 2014). However, as the sensation of pain during exercise is not only reliant on the noxious peripheral stimuli from skin and muscle nociceptors, but also the processing of this input in the primary sensorimotor cortex, secondary somatosensory cortex, anterior insular and cingulate cortex and thalamus (O'Connor and Cook 1999;Olesen et al 2012), the effect of pain on endurance performance can be assessed by blocking the input or moderating the processing of it.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggested that there was a significant difference, which indicates that during the whole understate session the participants' heart rate was significantly lower by 5-7 bpm, than during the control and overstate session. As explained above, HR is an objective measurement of a continuous physiological signal, which has been used in the assessment of clinical pain experiments [2], [25]. HR allows us to record physiological changes and correlations between exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whilst the sensory signal of pain for a given exercise intensity/duration is unavoidable, the intensity of pain that someone consciously experiences may not always be the same. Pain has an important role in protecting the body from damaging stimuli through avoidance behavior, and so pain during exercise may influence decision making that either results in the individual reducing the exercise intensity (so that pain is reduced), or withdrawing from the exercise entirely [2]. In either scenario, this could have negative consequences for the individual's physical activity level and/or training stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Luu et al [47] showed that by reducing muscle force using a neuromuscular blockade, sensations of heaviness were reduced, presumably due to reduced peripheral feedback associated with paralysis of muscle spindle intrafusal fibres, since it was assumed that motor command must have been elevated. Aligned with this hypothesis, it has recently been proposed that exerciseinduced pain is an important contributing factor in the regulation of work intensity and is thus important in pacing during exercise [57]. It has been shown that an opioid analgesic to selectively block the activity in ascending sensory pathways results in elevated RPE during a 5-km cycling time trial [58].…”
Section: Neural Regulation Of Perceptionsmentioning
confidence: 97%